(untitled) (Tamaddun, 2022)
The Independent National Electoral Commission (INEC) is the Electoral Management Body (EMB) established in Nigeria to deliver free, fair, and credible elections through a transparent and peaceful process. However, the origin of violence perpetrated during elections with wanton destruction of public and private property, including loss of lives all over the country, calls for an examination of the role of INEC in this regard. This study used historical method analyses to examine the role of INEC. The study found out that though INEC has, to a large extent, performed its role and also helped to deepen democracy in Nigeria since its establishment in 1998. Further studies also found that INEC’s poor organisational abilities, lack of essential transparency, widespread procedural irregularities, substantial evidence of fraud, widespread voter disenfranchisement at different stages of the process, etc., have been responsible for the numerous incidences of conflict in the country during elections. This paper concludes and recommends that external challenges, such as security, inadequate funding, and the desperation amongst Nigerian politicians, be moderated and curtailed with a synergy between the Legislature and Executive arms. At the same time, the judiciary plays its role well, including that INEC employs professional ethics amongst its staff with organisational and logistical efficiency and effectiveness in the electoral process. INEC’s role will be overtly transparent and therefore lead to the delivery of peaceful rather than conflict-infected elections.